The effect of reduced dose of PGF2α on certain reproductive parameters in awassi yearlings in anestrus synchronisation protocol following the end of the of the breeding season - Ozbilek, I; Ergun, Y; Gözer, A; Bahan, O; Alasahan, S (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of this study was to investigate the effect of the administration of half or full dose of prostaglandin F2α (PGF2α; Gestavet Prost, d-cloprostenol, HIPRA®) injection in a routine synchronization protocol following the end of the breeding period including intravaginal sponge (medroxyprogesterone acetate; Espanjovet, HIPRA®) and eCG (Oviser 500, HIPRA®) on certain fertility parameters in ewes.Two hundred thirty-eight Awassi yearlings (aged one year old) divided into two groups:116 ewes received a half dose (HSDP; 37.5 μg) of PGF2α and 122 ewes received full dose (FSDP;75 μg).The pregnancy rates were 67.2% and 72.1% for HSDP and FSDP, respectively (P>0.05). The lambing rates were 64.7% and 63.9% for HSDP and FSDP, respectively (P>0.05).The single lambing rate in HSDP(94.7%) was higher (P<0.05) compared to that in FSDP (73.1%). The twin and multiple birth rates of FSDP was higher (P<0.05) than HSDP. As a result, it was inferred that aHSDP could be used in Awassi yearlings without experience of lamb care and in a herd in which single lambing was preferable. Moreover, due to the fact that it is more affordable and not detrimentalto fertility, it was concluded that HSDPcan offer an advantage in large flocks and can be used for manipulating fecundity ratesin yearlings.